Das Lieferkettengesetz in der Praxis: Einschätzungen durch Betriebsräte - Florian Blank; Wolfram Brehmer (Wirtschaftsdienst, 2024)
The Act on Corporate Due Diligence Obligations in Supply Chains places big enterprises under the obligation to analyse their supply chains regarding risks of human rights violations, and to develop preventative measures. This article uses data from a 2023 survey of works councils to show which corporations are affected by the law and which companies have enacted measures to combat human rights violations. Corporations that are not affected by the law are also analysed to understand the law's impact. Also, the article shows which groups (management, the finance committee, the works councils and employees) have dealt with the topic, and whether works councils receive enough information about this topic.
Keywords: F66; J59; J83; 330